AN EMPIRICAL STUDY ON THE USAGE OF DIGITAL BANK IN INDONESIA - Mailoa, Betha Zionetha; Tjhin, Viany Utami (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Nowadays, information technology plays an important role as a support for daily activities. The role of this information technology is to provide convenience for its users. The development of information technology in banking is developing rapidly, until now there are digital banks. Therefore, the purpose of this study is to find out the factors that influence customers in the use of digital banks, especially in Indonesia. The research model used in this study is the UTAUT model with the addition of variables fear of financial loss, perceived identity theft, and security & privacy, with behavioral intention and security & privacy as moderation variables. In order to obtain data, data collection in the study was carried out by distributing questionnaires through Google Forms. From the questionnaire distributed, the results of 100 respondents of digital bank users were obtained. The results showed that the variables that have the most significant direct influence on Use Behavior in the use of bank digital applications are rerformance expectancy and security & privacy. Meanwhile, effort expectancy can be concluded that it does not have a significant influence on variable use behavior in digital banks, because both through variable moderation and direct effect, the Effort Expectancy factor does not have a significant influence.